Offline political engagement leads to online political voice among Kyrgyzstan bloggers. Issue 3 (2nd October 2017) - Kurambayev, Bahtiyar; Masullo Chen, Gina
Abstract : Results of a survey of student bloggers in the former Soviet Bloc nation of Kyrgyzstan ( N  = 132) showed that their offline political engagement had a positive relationship with their online political voice. Specifically, those bloggers who attended political meetings or had contacted a politician or civil servant offline were more likely to express their political thoughts on their blog. Results also showed that those who paid the most attention to political and public affairs reports in newspapers, blogged more frequently, and those who blogged more frequently, exhibited greater expression of political voice through their blogs. In addition, media attentiveness showed an indirect effect on online political voice, mediated through blogging frequency. Results are discussed in relation to social capital theory and implications for political expression in this country where speaking out remains constrained are explored.